Evaluation of Propolis from Kurdistan region as a new resinous sealer in root canal obturation-part I biocompatibility study - Dara Hama; Al-Huwaizi, Hussain F; El-Samarri, Salim A (Journal of Baghdad College of Dentistry, 2013)
Background: Many materials were proposed as root canal obturating materials but the biocompatibility issue remains to be a critical one. Propolis has been used as a therapeutic agent since the time of Hippocrates. It is known that propolis exhibits some pharmacological activities, such as antibacterial, antiviral, antifungal and anti inflammatory activity. Materials and methods: Eighteen albino rats were used in the study and divided randomly into three groups of 6 animals for each group. Each group was scheduled to be sacrificed at different time periods, which were three days, one week and three weeks. Propolis and ZOE sealer implants of 4mm in diameter and 0.5 gm in weight were implanted in the dorsal side of the rats. At the end of the implantation, the rats were scarified and the histopathological picture was made to the implantation site. Results: Zinc oxide eugenol sealer showed severe inflammation after 3 days of implantation whci subsided after 7 days. After 21 days, moderate inflammatory reaction was evident. Propolis presented moderate reaction after 3 and 7 days but with presence of signs of collagen fiber formation. After 21 days, connective tissue capsule was present. Conclusion: Propolis presented better biocompatibility than zinc oxide eugenol sealer.